1995
DOI: 10.1152/jn.1995.73.6.2553
|View full text |Cite
|
Sign up to set email alerts
|

Different Ca2+ channels in soma and dendrites of hippocampal pyramidal neurons mediate spike-induced Ca2+ influx

Abstract: 1. Intracellular recordings, in conjunction with fura-2 fluorescence imaging, were used to evaluate the contribution of the different Ca2+ channel subtypes to the Ca2+ influx induced by back-propagating trains of action potentials. High-threshold channels contributed mainly to Ca2+ influx in pyramidal cell somata and proximal dendrites, whereas low-threshold and other Ni(2+)-sensitive channels played a greater role in more distal dendritic signaling. These data suggest that the different Ca2+ channel types par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
123
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(140 citation statements)
references
References 32 publications
15
123
1
1
Order By: Relevance
“…Unlike in hippocampal pyramidal neurons (Christie et al, 1995;Magee and Johnston, 1995) the densities and distributions of calcium channel subtypes have not been characterized in L2/3 neurons. We therefore cannot exclude the possibility that distal dendritic channels are more sensitive to predepolarization than those in the proximal dendrite.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in hippocampal pyramidal neurons (Christie et al, 1995;Magee and Johnston, 1995) the densities and distributions of calcium channel subtypes have not been characterized in L2/3 neurons. We therefore cannot exclude the possibility that distal dendritic channels are more sensitive to predepolarization than those in the proximal dendrite.…”
Section: Discussionmentioning
confidence: 99%
“…An interaction of N-V DCC s with the cytoskeleton is supported by the polarized distribution (Jones et al, 1989;Westenbroek et al, 1992;Mills et al, 1994;Christie et al, 1995) and the immobility of Ͼ70% (Jones et al, 1989) of N-VDCCs in mature hippocampal neurons and by the fact that the first postnatal week is a major phase for maturation of the neuronal cytoskeleton (Burgoyne, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the efficacy of CA1 synapses is reported to be high [release probability (P r ) close to unity] in very young (P4 -P6) hippocampi but diminishes to a lower level (P r Ͻ0.5) with maturation (Bolshakov and Siegelbaum, 1995). A purely presynaptic role for N-V DCC s is probably unlikely, however, because N-VDCCs also are found on hippocampal dendrites (Jones et al, 1989;Westenbroek et al, 1992;Mills et al, 1994;Christie et al, 1995) and their spines (Mills et al, 1994). Although the functional contribution such postsynaptic N-VDCCs make is unclear (Mills et al, 1994;Elliott et al, 1995), one plausible role is to direct afferent axons to discrete synapses.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53] For example, in CA1 pyramidal neurons where Ni 2C dependent synaptic plasticity mechanisms have been described at the Schaffer collateral synapses, 19,39 Ni 2C sensitive channels are more abundant in the distal area of the apical dendrites. 54 Accordingly, by recording field potentials at different locations, "proximal," "middle" and "distal" along the apical dendrite of CA1 pyramidal neurons, Isomura et al 55 showed that while no significant difference among the magnitudes of the induced LTP was observed at these 3 dendritic locations in control condition, Ni 2C strongly inhibited the LTP induction in distal dendrites, slightly in middle dendrites, and did not significantly influenced LTP at proximal dendrites. Thus, for a given synaptic type, the specific T-(R) channel distribution may underlie different induction mechanisms of LTP along a dendrite.…”
Section: Subcellular Localization Of T-type Channels and Synaptic Plamentioning
confidence: 99%